Condition-dependent reproductive effort in frogs infected by a widespread pathogen - Roznik, Elizabeth A. (Proc Biol Sci, 2015)
To minimize the negative effects of an infection on fitness, hosts can respond adaptively by altering their reproductive effort or by adjusting their timing of reproduction. We studied effects of the pathogenic fungus Batrachochytrium dendrobatidis on the probability of calling in a stream-breeding rainforest frog (Litoria rheocola). In uninfected frogs, calling probability was relatively constant across seasons and body conditions, but in infected frogs, calling probability differed among seasons (lowest in winter, highest in summer) and was strongly and positively related to body condition. Infected frogs in poor condition were up to 40% less likely to call than uninfected frogs, whereas infected frogs in good condition were up to 30% more likely to call than uninfected frogs. Our results suggest that frogs employed a pre-existing, plastic, life-history strategy in response to infection, which may have complex evolutionary implications. If infected males in good condition reproduce at rates equal to or greater than those of uninfected males, selection on factors affecting disease susceptibility may be minimal. However, because reproductive effort in infected males is positively related to body condition, there may be selection on mechanisms that limit the negative effects of infections on hosts.